2021
DOI: 10.1371/journal.pone.0257069
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning model for predicting the optimal depth of tracheal tube insertion in pediatric patients: A retrospective cohort study

Abstract: Objective To construct a prediction model for optimal tracheal tube depth in pediatric patients using machine learning. Methods Pediatric patients aged <7 years who received post-operative ventilation after undergoing surgery between January 2015 and December 2018 were investigated in this retrospective study. The optimal location of the tracheal tube was defined as the median of the distance between the upper margin of the first thoracic(T1) vertebral body and the lower margin of the third thoracic(T3) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…3 to 5 min to be perfected by muscle relaxation and then tracheal intubation was performed under visual laryngoscope. (catheter diameter (with sleeve) = age/4 + 4; catheter insertion depth through the mouth = age/2 + 12 cm) [ 13 ]. After auscultation of clear and symmetrical respiratory sounds in both lungs, the cannula was properly fixed and connected to the anesthesia machine to control respiration, ventilation mode: volume-controlled ventilation, inspired oxygen concentration 50%, tidal volume 8-10 ml/kg, minute ventilation volume 100-200 ml/kg, respiratory rate 14-18breaths/min, inspiration-expiration ratio 1:2, peak inspiratory pressure 12-20cmH 2 O (the upper-pressure limit should not exceed the maximum 28cmH 2 O), end-tidal carbon dioxide (ETCO 2 ) is maintained at 35-45 mmHg, and respiratory rate and tidal volume are adjusted according to ETCO 2 [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…3 to 5 min to be perfected by muscle relaxation and then tracheal intubation was performed under visual laryngoscope. (catheter diameter (with sleeve) = age/4 + 4; catheter insertion depth through the mouth = age/2 + 12 cm) [ 13 ]. After auscultation of clear and symmetrical respiratory sounds in both lungs, the cannula was properly fixed and connected to the anesthesia machine to control respiration, ventilation mode: volume-controlled ventilation, inspired oxygen concentration 50%, tidal volume 8-10 ml/kg, minute ventilation volume 100-200 ml/kg, respiratory rate 14-18breaths/min, inspiration-expiration ratio 1:2, peak inspiratory pressure 12-20cmH 2 O (the upper-pressure limit should not exceed the maximum 28cmH 2 O), end-tidal carbon dioxide (ETCO 2 ) is maintained at 35-45 mmHg, and respiratory rate and tidal volume are adjusted according to ETCO 2 [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, machine learning techniques (artificial neural network, random forest, elastic net and support vector machine) have been used to predict optimal depth of tracheal tube tip using data such as age, weight, height and gender [29]. This can guide physicians when planning for appropriate airway management, and may ultimately reduce the frequency of unintentional endobronchial intubations.…”
Section: Models For the Selection Of Airway Devicesmentioning
confidence: 99%
“…An endotracheal intubation training program using virtual reality (VR) has been developed in airway management by applying an ML technique through user feedback 21 . In addition, our previous study demonstrated that ML could predict the appropriate intubation depth more accurately than the conventional formula-based method in pediatric patients 22 . However, the sample size used in the study was very small.…”
Section: Introductionmentioning
confidence: 96%